Pelimpahan Kuota Haji Jamaah Wafat: Tinjauan Maqāṣid al-Syarī‘ah dan Psikologis - Mulyadi, Kiking; Supriatna, Encup; Fahmi, Irfan (Sekolah Tinggi Ilmu Syariah Wal Aqidah Ash-Shofa Manonjaya, 2026)
The transfer of Hajj quotas for pilgrims who pass away before departure raises debates from both Islamic law and Indonesian positive law perspectives. This study aims to analyze the issue through three dimensions: Islamic legal views, the maqāṣid al-sharī‘ah framework, and the psychological implications for the deceased pilgrim’s family. Using a qualitative, literature-based approach, the findings indicate that quota transfer is permissible as an administrative right, not an inheritable one, provided it is implemented fairly and transparently. From the maqāṣid al-sharī‘ah perspective, such a policy supports the preservation of religion (ḥifẓ al-dīn) and life (ḥifẓ al-nafs), as long as it does not harm other pilgrims in the waiting list. Psychologically, it offers comfort to the bereaved family but requires strict supervision to prevent perceptions of injustice. Therefore, the transfer of Hajj quotas should be regulated and monitored carefully to align with justice and public welfare principles.